Reimagining Islamic Civilization in the Age of AI: Digital Humanities, Ethical Challenges, and Knowledge Production in the Muslim World - Yusuf, Muhammad (Sekolah Tinggi Agama Islam Kuningan, 2025)
Background: The convergence of artificial intelligence with Islamic civilization presents unprecedented challenges to knowledge production, ethical frameworks, and educational practices. Despite producing substantial scholarship on Islam–AI intersections, Muslim-majority regions continue to experience systematic exclusion from global AI governance, raising concerns about epistemic marginalization and ethical representation in emerging technologies.Objective: This study aims to map the global landscape of Islamic–AI scholarship, analyze dominant Islamic ethical frameworks guiding AI development, evaluate digital humanities applications to Islamic textual traditions, and assess challenges related to AI integration in Islamic education.Method: The study employs bibliometric mapping using VOSviewer and Biblioshiny on 1,060 Scopus-indexed documents published between 1969 and 2024, complemented by critical digital humanities analysis, interpretive literature review, and a survey of 1,847 Islamic education stakeholders across 23 countries. Computational text analysis supports qualitative and quantitative assessments.Findings and Implications: Results indicate a geographic concentration of research output in Southeast Asia (42%) and the Middle East (23%), despite continued marginalization from global AI governance structures. The maqāṣid al-sharīʿah framework dominates 78% of Islamic AI ethics publications, yet only 23% of institutions have implemented formal ethical protocols. Digital humanities applications achieve 89% OCR accuracy for printed Arabic texts and 71% for manuscripts. Acceptance of AI in Islamic education varies significantly by generation and institutional type.Conclusion: The findings highlight an urgent need to decolonize AI knowledge production, diversify Islamic ethical frameworks beyond maqāṣid-centric approaches, develop contemplative computing methodologies aligned with Islamic epistemology, and implement hybrid pedagogical models that preserve relational dimensions of Islamic education while responsibly leveraging AI technologies.